Ionic Liquid‐based Microchannels for Highly Sensitive and Fast Amperometric Detection of Toxic Gases. Issue 1 (13th November 2018) - Ge, Mengchen; Hussain, Ghulam; Hibbert, D. Brynn; Silvester, Debbie S.; Zhao, Chuan
Abstract: Ionic liquid (IL)‐based microchannels sensors have been fabricated and employed for the detection of toxic ammonia (NH3 ) and hydrogen chloride (HCl) gases, with enhanced sensitivity and response times compared to conventional electrodes. Electrochemical techniques were employed to understand the behaviour of these highly toxic gases in two ionic liquids, [C4 mpyrr][NTf2 ] and [C2 mim][NTf2 ], on a gold modified microchannels electrode. The limits of detection (LODs) obtained in [C4 mpyrr][NTf2 ] for NH3 (3.7 ppm) and in [C2 mim][NTf2 ] for HCl (3.6 ppm) were lower than the current Occupational Safety and Health Administration Permissible Exposure Limit (OSHA PEL) for the two gases (25 ppm for NH3 and 5 ppm for HCl). The response time of the sensor is 15 s with a sensitivity of 143 nA ppm −1 and 14 nA ppm −1 for HCl and NH3, respectively. These results demonstrate the superiority of IL‐based microchannels sensors for detecting toxic gases, when compared to commercially available sensors or traditional IL‐based sensor designs, where high sensitivity or fast response time is still a challenge. Abstract :